Cost-effectiveness of groin hernia repair from a randomized clinical trial comparing commercial versus low-cost mesh in a low-income country. Issue 6 (16th February 2017) - Löfgren, J; Matovu, A; Wladis, A; Ibingira, C; Nordin, P; Galiwango, E; Forsberg, B C
Abstract: Background: Over 200 million people worldwide live with groin hernia and 20 million are operated on each year. In resource-scarce settings, the superior surgical technique using a synthetic mesh is not affordable. A low-cost alternative is needed. The objective of this study was to calculate and compare costs and cost-effectiveness of inguinal hernia mesh repair using a low-cost versus a commercial mesh in a rural setting in Uganda. Methods: This is a cost-effectiveness analysis of a double-blinded RCT comparing outcomes from groin hernia mesh repair using a low-cost mesh and a commercially available mesh. Cost-effectiveness was expressed in US dollars (with euros in parentheses, exchange rate 30 December 2016) per disability-adjusted life-year (DALY) averted and quality-adjusted life-year (QALY) gained. Results: The cost difference resulting from the choice of mesh was 124·7 (€118·1). In the low-cost mesh group, the cost per DALY averted and QALY gained were 16·8 (€15·9) and 7·6 (€7·2) respectively. The corresponding costs were 58·2 (€55·1) and 33·3 (€31·5) in the commercial mesh group. A sensitivity analysis was undertaken including cost variations and different health outcome scenarios. The maximum costs per DALY averted and QALY gained were 148·4 (€140·5) and 84·7 (€80·2) respectively. Conclusion: Repair using both meshes was highly cost-effective in the study setting. A potential cost reduction of over 120 (nearly €120) per operation with use of the low-cost mesh is important if the mesh technique is to be made available to the many millions of patients in countries with limited resources. Trial registration number: ISRCTN20596933 (http://www.controlled-trials.com ). Abstract : Mosquito mesh is cost-efficient